A global review of racial, ethnic and socio-economic disparities in multisystem inflammatory syndrome in children related to COVID-19 - Asghar, Zoha; Sharaf, Kanza; Butt, Faran Ahmed; Shaikh, Omer Ahmed; Shekha, Manahil; Waris, Abdul; Ullah, Irfan; Nashwan, Abdulqadir J. (Frontiers in Public Health, 2022)
With over 500 million confirmed cases and 6.2 million deaths worldwide, the novel coronavirus has highlighted the underlying disparities in healthcare, unpreparedness to deal with a new disease and the need for monitoring and surveillance for a post-infectious syndrome as well as complicated diseases. Initially, children were thought to be spared but reports of a new phenomenon manifesting as Kawasaki-like disease, toxic shock syndrome, and multi-system inflammatory syndrome, which developed after a few weeks of severe COVID-19 infection, emerged in the pediatric population. As the pandemic progressed, increased prevalence of multi-system inflammatory syndrome in children (MIS-C) related to COVID-19 was seen in non-Hispanic blacks, Asians, and Latinos as compared to the white population drawing attention to a possible role of ethnicity and socio-economic disparities. The CDC currently reports that 31% of MIS-C cases were seen in Black Non-Hispanics and 26% in Latinos, who were historically more affected in previous pandemics. Furthermore, MIS-C cases in developing countries showed higher mortality as compared to high-income countries, which points toward the role of social determinants of health and limitations in a low-resource set up in increasing the disease burden of MIS-C, which should be treated as a public health emergency. Our review highlights the role of ethnicity, socio-economic factors, comorbidities, and differences in populations affected by MIS-C in high-income vs. low- and middle-income countries.